Improving Quality and Performance of Facility Management Using Building Information Modelling - Chong, Heap Yih; Wang, Jun; Shou, W.; Wang, Xiangyu; Guo, J. (Springer, 2014)
Poor facility management has been attributed to lack of coordination and information during the maintenance process. The need for high quality applies not only to construction works and workmanship, but is also for its subsequent coordination and maintenance of a building. The paper aims to improve quality and performance of maintenance by integrating an advanced technology with a managerial approach, namely, building information modelling (BIM) and facility management. A BIM case study was investigated, which was located in Shanghai, China. Five significant areas were identified to improve the quality and performance of facility management, namely, centralized system, visualization, simplification, modifiable system, and smart emergency escape. The results highlight the benefits in applying the integrated system between BIM and facility management. It draws an insightful inference in enhancing quality services in facility management.